Characteristics of institutionalized young onset dementia patients – the BEYOnD study. (8th October 2014) - Mulders, A.J.M.J.; Zuidema, S.U.; Verhey, F.R.; Koopmans, R.T.C.M.; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: People with Young Onset Dementia (YOD) have specific needs for care. These people eventually require institutional care, usually delivered by institutions designed for the elderly. The Dutch network of care organizations delivering specialized YOD care offers a unique opportunity to obtain more knowledge of this special population. Methods: Our cross-sectional study collected data from 230 people with YOD in eight care homes providing YOD specialized care. Data collected: demographic data, disease duration, dementia subtype, comorbidity, dementia severity (Global Deterioration Scale – GDS), neuropsychiatric symptoms (NPS; Neuropsychiatric Inventory – NPI, Cohen Mansfield Agitation Inventory – CMAI), disease awareness (Guidelines for the Rating of Awareness Deficits – GRAD), need for assistance (hierarchic Activities of Daily Living (ADL) scale – Resident Assessment Instrument – Minimum Data Set (RAI-MDS)). Results: The mean age of the residents with YOD in care homes was 60 years and 53% of them were men. There is a large variety of etiologic diagnoses underlying the dementia. Dementia severity was very mild to mild in 18%, moderate in 25%, and severe or very severe in 58% of the participants. The prevalence of NPS was high with 90% exhibiting one or more clinically relevant NPS. Comorbidity was present in more than three quarters of the participants, most frequently psychiatric disorders. Conclusions: The institutionalized YOD population is heterogeneous. NPS occur in almost all institutionalized people with YOD, and frequency and severity of NPS are higher than in late onset dementia (LOD) and community-dwelling YOD patients. Care should be delivered in settings accommodating a mixed male and female population, with appropriate, meaningful activities for all individuals. Further research is needed on NPS in YOD, to enhance quality of life and work in specialized YOD-care.